VERIFICATION MODEL FOR THE SYSTEMS WITH LIMITED RESOURCES - Tabunshchyk, G. V.; Kapliienko, T. I.; Shytikova, O. V. (Radio Electronics, Computer Science, Control, 2018)
Context. In the article the task of systems with limited resources verification is considered. One of the challenges for implementation of concurrent minicomputer systems for implementations its in real products is high requirements to the limited hardware. As a result it course additional requirements for them and limited the sphere of their implementation especially in critical real-time systems in medicine or defense industry. That’s why development verification tools for minicomputer systems is actual task. The object of the research – the process of modelling of reconfiguring systems with limited resources functionality. Objective – to improve reliability of systems with limited resources by ensuring of data integrity and automating of the verification process. Method. The model of systems with limited resources verification based on the verification model of web-oriented systems is obtained, which describes the verified components of objects and the way of data exchange based on the dynamic model of data transmission. The concept of “functional unit” has been modified by adding hardware blocks, which makes it possible to automate the testing of these elements. The advantage of this model is that it collect results of verification of the devices connected to the minicomputers systems and describes the optimal period for reading archive files, which improve the relevance and integrity of test results for systems with limited resources. As a case study, the architecture of a minicomputer system based on Raspberry Pi was considered by the authors. Results. Developed model was applied for the verification of the remote laboratory for reliability tasks (ISRT). Conclusions. In the article the modified model for system with limited resources verification is suggested, which in contrast to web-oriented verification model describes adaptive architecture of the embedded systems and use model for data transition into the external storage, which make possible to implement this model for variety of hardware configurations.